L’agriculture multifonctionnelle comme écrin pour la ville durable : une vision urbaine des liens entre la ville et l’agriculture en Méditerranée ? - Coline Perrin (Bulletin de l’Association de Géographes Français, 2013)
With the proliferation of research on the links between cities and agriculture, the figure of suburban farming threatened by urban sprawl has given way to a new image of multifunctional agriculture serving as a backdrop - even contributing - to the development of sustainable cities. In this paper, we test this hypothesis by analyzing the inclusion of agriculture in urban projects of two municipalities near Aix -en-Provence and Florence, where vineyards and olive groves have been preserved urbanization. Our results show that an urban approach to agriculture by its amenities does not provide sustainability for agriculture or the city. Securing agricultural land in the local planning documents in these two case studies is a critical factor in maintaining agriculture, but in the long-term insufficient in the absence of economic dynamism of the agriculture or joint projects allowing agricultural and urban local stakeholders to agree on the expected functions of agriculture.